Could the Interaction between Arbuscular Mycorrhizal Fungi and Biostimulants Improve the Plant Physiological Status of Prosopis alba Seedlings? - Santacruz-García, Ana Carolina (2022)
Presentado al 3rd International Electronic Conference on Forests—Exploring New Discoveries and New Directions in Forests, 15–31 October 2022